Metode Vulnerability Assesment Dalam Pengujian Kinerja Sistem Keamanan Website Points of Sales - Wahyudin, Wahyudin; Kuswara, Heri; Resti, Resti; Dalis, Sopiyan (LPPM Universitas Bina Sarana Informatika, 2024)
The development of electronic commerce through point of sales based websites is closely related to the growth rate of the internet, because electronic commerce runs through networks and Internet connections. However, the more point of sale based websites that are built, the greater the possibility of cyber attacks that could harm the website. Therefore, website security is very important to pay attention to. One method that can be used to maintain website security is to carry out a Vulnerability Assessment. Vulnerability Assessment is a process of searching for security gaps in an information system or computer network with the aim of identifying potential security vulnerabilities and taking preventative steps before an attack occurs. The vulnerability assessment technique used is using a weakness scanner application to identify security gaps in systems and applications such as Nikto, Nmap, Zenmap and Owasp ZAP. Based on testing with the Owasp ZAP tool, the results of scanning carried out on the sakupos.com website, which is a points of sales based website, show that there is a vulnerability on the website. The test results show the Level of Vulnerability (Risk Assessment) as well as recommended solutions that can be used to prevent it. There were 10 vulnerabilities detected, 7 vulnerabilities were found with a Medium risk level, 2 vulnerabilities with a Low risk level, and 1 other vulnerabilities at the Informational risk level.